Use of Internet among banks in Singapore - Wee, Kok Ping. (2009)
Internet was first introduced to Singapore in late 1991. Since then, the popularity of Internet has been a phenomenon that caught on with Singaporeans from all walks of life. With the Singapore government's push for using Information Technology (IT) to gain strategic competitiveness, more and more local and foreign corporations are now looking into making use of Internet as another means of communication, as well as conducting business over the Internet, where the term Electronic Commerce is used.